Sustainable Livestock Production in The Perspective of National Food Security Policy - Tjeppy D Soedjana (Indonesian Center for Animal Research and Development, 2013)
This paper presents an overview of the role that livestock play in various dimensions of food security. Food security is defined as a state of affairs where all people at all times have access to safe and nutritious food to maintain a healthy and active life. Availability, accessibility, and affordability of individuals to consume food according to their respective socio-economic conditions are important dimensions. It describes the place of livestock products in human nutrition, the contribution of livestock to the national food supply and the way that livestock can affect food access, as a direct source of food and a source of income. Access to food is the most basic human right, especially for Indonesia with more than 240 million people with annual growth of 1.3%. To secure food availability, a sustainable food production growth more than 2% per year, including animal protein sources, is needed. It is necessary to strengthen food supply by maximizing available resources; improve food distribution system to guarantee a stable food supply and public access; encourage diversified food consumption; and prevent as well as resolve food scarcity. Furthermore, within the national objectives for self-sufficiency in rice, corn, soybean, and white sugar, the current annual percapita consumption of livestock products has reached 6.96 kg (meat), 7.3 kg (eggs) and 16.5 kg (milk), which indicates good progress to stimulate sustainable domestic livestock production. Key words: Food security, sustainability, livestock production